2022
DOI: 10.3390/rs14133143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deep Learning Methods for Detecting and Counting Sorghum Heads in UAV Imagery

Abstract: With the rapid development of remote sensing with small, lightweight unmanned aerial vehicles (UAV), efficient and accurate crop spike counting, and yield estimation methods based on deep learning (DL) methods have begun to emerge, greatly reducing labor costs and enabling fast and accurate counting of sorghum spikes. However, there has not been a systematic, comprehensive evaluation of their applicability in cereal crop spike identification in UAV images, especially in sorghum head counting. To this end, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Research on the detection of grain from UAV imagery was conducted by Li, Wang, and Huang [25]; the authors compared SSD to YOLOv4 and reported the latter to be superior. Another research [26] study evaluated SSD and faster R-CNN algorithms for human detection in aerial thermal images.…”
Section: Ssd Algorithmmentioning
confidence: 99%
“…Research on the detection of grain from UAV imagery was conducted by Li, Wang, and Huang [25]; the authors compared SSD to YOLOv4 and reported the latter to be superior. Another research [26] study evaluated SSD and faster R-CNN algorithms for human detection in aerial thermal images.…”
Section: Ssd Algorithmmentioning
confidence: 99%
“…Therefore, it is necessary to find a rapid and highly accurate detection method for the emergence rate of soybean seedlings that is suitable for large-scale areas. In modern precision agriculture, it is becoming increasingly important to use computer vision technology and UAV remote sensing technology to address the challenge of monitoring soybean seedling emergence rate, especially for early breeding decisions and the implementation of reseeding work [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the generalization ability of these methods drops significantly when the application domain or environment changes [9,10]. With the rapid development of artificial intelligence technology, deep learning-based object detection methods have demonstrated excellent performance in the agricultural field, introducing innovative possibilities for detecting various crops, including wheat [11], maize [12], sorghum [13], rice [14], and others [15]. These methods are mainly classified into two categories: pixel-based semantic segmentation and target-based detection.…”
Section: Introductionmentioning
confidence: 99%